First Phantom-Based Quantitative Assessment of Scandium-44 Using a Commercial PET Device - Lima, Thiago V. M.; Gnesin, Silvano; Nitzsche, Egbert; Ortega, Pablo G.; Müller, Cristina; van der Meulen, Nicholas P. (Frontiers in Physics, 2020)
Scandium (Sc) is a promising candidate for theranostic applications due to the existence of radioisotopes suitable for both imaging and therapy. A “proof-of-concept” study regarding first-in-human use of 44Sc for imaging metastatic neuroendocrine tumours was reported recently, however, quantitative assessment of 44Sc-based PET images was not performed. The aim of this study was to evaluate quantitative capabilities of 44Sc-PET using a commercial PET scanner. The NEMA/IEC body phantom with 44Sc was acquired according to the local protocol used for whole-body oncological [18F]FDG PET examinations. Additionally, we characterised the signal recovery (recovery coefficient - RC) according to the iteration number. For all reconstructions, pertinent image corrections (normalisation, dead time, activity decay, random coincidence and attenuation) were applied. Presently, 44Sc scatter corrections are not optimised and could, thus, result in quantitative bias. To investigate the best option, the data were reconstructed using different available scatter corrections (relative -RelSC- and absolute AbsSC) and an additional prompt-gamma correction (PGC). System cross-calibration with the local dose calibrator (BGcal) and image noise, expressed by the coefficient of variation (COV), were evaluated in the homogeneous background region (5 kBq/mL) of the phantom. Maximum (RCmax) and 50% threshold recovery coefficients, corrected for background (RCA50), were measured for all spherical inserts (25 kBq/mL) of the phantom. Acceptable COV (<15%) was achievable with low iteration numbers (<3). BGcal differences were low: mean BGcal were 77.8% , 81.3% and 86.7%, for RelSC, AbsSC and PGC, respectively. RC values exceeded the present RC range recommended for [18F]FDG procedures. Using the iterations to be evaluated, RCA50 ranged from 29.9% to 59.9% for the smallest lesion (spherical insert of 10 mm diameter) and from 45.5% to 80.3% (13 mm), 66.4% to 75.6% (17 mm), 71.7% to 75.7% (22 mm), 75.1% to 78.6% (28 mm) and 76.7% to 80.9% (37 mm) for the respectively spherical inserts. The results of this study show that clinical 44Sc-PET imaging has the potential to provide signal recovery in lesions of different sizes comparable to current 18F-PET standards. In order to improve the quantitative accuracy of 44Sc PET, optimised corrections are still necessary and will be investigated further in future.